Does Born Global Survival Differ From Other Start-Ups? Employee- versus Firm-level Resources - Braunerhjelm, Pontus; Halldin, Torbjörn (Senate Hall, 2022)
In this paper we embark from a resource-based view to explain hazard rates among new firms. Whereas previous research primarily has approximated firms’ resource bases with size and performance variables (e.g., productivity), we differentiate between employee- and firm-level components, analyzing firm survival. We focus on born global firms within both the manufacturing and knowledge-intensive services (KIBS) industries while implementing three broader control groups. Using longitudinal data we implement a Cox proportional hazard model to estimate the hazard ratios of the included employee- and firm-level variables. Both industry- and firm-level differences are identified, even though the results vary with the specification of the estimations and the particular group being examined. The results should be relevant for both managers and policymakers.
Keywords: born global firms|survival|resource base|hazard rates